Literature Review: Anxiety on Patiens with Myocardial Infarction - Friska Sinaga (STIKes Panti Rapih, 2020)
Background: Myocardial Infarction is one of the major cardiac event that cause of death in the world. One of the first reaction to myocardial Infarction is anxiety, which is a natural response to a life threatening event. High level of anxiety was associated with a higher rate of all cause cardiovascular complication and mortality in the first 3 years following myocardial infarction onset. Objective: This paper purposed to review the best evidence, guideline, or protocol to prevent and control anxiety in patients with myocardial infarction. Methods: A range database was searched to identify studies addressing programs to increase physical function of elderly with heart failure including CINAHL, Proquest, PubMed, and manual searching from the reference list of previous obtained articles. Studies published in English 2006-2015 were included. Results: There were ten studies in the final dataset. Factors related with anxiety were assessed in each study as characteristic and baseline studies. Studies reviewed intervention program to reduce anxiety including health education, relaxation, back massage therapy, whole massage therapy and combination between two interventions. Conclusion: Anxiety management that nurses can use not only health education by giving information about their diseases but they can also give intervention that can decrease their anxiety such as massage and relaxation or by combing together between health education and massage and relaxation. Keywords: anxiety, relaxation, massage, education, myocardial infarction